Predatory birds in agroforestry: Dawn of a new era for biological control from multitrophic interactions - Tanmaya Kumar Bhoi; Ipsita Samal; Biswaranjan Behera; Deepak Kumar Mahanta; J. Komal; R. Athulya (Avian Research)
Ensuring food security for a rapidly growing global population amidst resource limitations and climate change is a major challenge. Agroforestry an ecologically sustainable land-use system that integrates trees, crops, and sometimes livestock offers significant promise by enhancing biodiversity, ecosystem services, and agricultural productivity. A central concern in such systems is pest management, which traditionally relies on chemical pesticides. However, their excessive use has led to environmental degradation, pest resistance, and health hazards. This review explores the potential of insectivorous birds as natural pest control agents in agroforestry systems. It focuses on how habitat features, vegetation complexity, and species-specific behaviors influence bird-mediated biological control. Insectivorous birds manage pest populations through direct predation, targeting a range of insect pests including caterpillars, beetles, and grasshoppers. Their foraging activity helps maintain pest populations below the economic threshold. Vegetation strata comprising ground cover, shrubs, understory, and canopy offer diverse foraging niches and nesting habitats that enhance bird diversity and functional roles. Pest control efficiency is closely linked to seasonality, resource availability, and habitat structure. Differentiating between beneficial (predatory) and pestiferous birds is essential to maximize ecosystem services and minimize crop losses or damage to beneficial insects. Conservation of beneficial bird species, informed vegetation planning, and regular monitoring are vital to strengthening multitrophic interactions and achieving sustainable pest control. Future research should focus on bird behavior, predator-prey interactions, and habitat management to optimize bird-friendly pest regulation strategies in agroforestry landscapes.